Alokasi Pemanfaatan Lahan Komoditas Unggulan Tanaman Pangan di Kabupaten Purwakarta - Desy Fatmawati; Dwi Putro Tejo Baskoro; Dyah Retno Panuju (Institut Pertanian Bogor, 2023)
Purwakarta Regency is one of the regencies in West Java Province that plays an essential role in agricultural development. One of the efforts to encourage sustainable agricultural development is by developing potential commodities so that scenarios can be drawn up that are in accordance with the region's potential. Optimum land use scenarios with several constraint targets need to be prepared by considering food needs, ecological sustainability, and farm income. This study aims to identify land available for food commodities and simulate the land use allocation of food commodities in Purwakarta Regency to meet food needs, farm income, and tolerance for erosion. Location quotient index, shift-share analysis, land suitability & capability analysis, and Multiple Goals Programming were used to achieve research objectives. The identified leading commodities are peanuts, cassava, and sweet potato. We suggest 15 classes of land available for optimum land use allocation. Space optimization is organized into four scenarios considering erosion control targets, meeting farmers' minimum incomes, and rice production. The smallest erosion is 13,159 tons/ha/year, while the highest possible income is IDR300,500,000,000. The highest rice production is 202.070 tonsGKP, cassava production is 16,919 tons, sweet potato is 2.014 tons, and peanut production is 531 tons. Achieving production targets can support agricultural development and food security improvement programs through sustainable production improvement. Keywords: erosion, farming, income, land suitability, MGP